Internationalization strategies of multi‐product firms: The role of technology - Baumgarten, Daniel; Irlacher, Michael; Mayr‐Dorn, Karin (Canadian Journal of Economics/Revue canadienne d'économique)
Abstract High‐performance firms typically have two features in common: (i) they produce in more than one country and (ii) they produce more than one product. In this paper, we analyze the internationalization strategies of multi‐product firms. Guided by several new stylized facts, we develop a theoretical model to determine optimal modes of market access at the firm–product level. We find that the most productive firms sell core varieties via foreign direct investment and export products with intermediate productivity. Shocks to trade costs and technology affect the endogenous decision to export or produce abroad at the product‐level and, in turn, the relative productivity between parents and affiliates.

Dissecting between-plant and within-plant wage inequality – Evidence from Germany - Baumgarten, Daniel; Felbermayr, Gabriel; Lehwald, Sybille (Industrial Relations: A Journal of Economy and Society)
Using rich linked employer–employee data for (West) Germany between 1996 and 2014, we conduct a decomposition analysis based on recentered influence function (RIF) regressions to analyze the relative contributions of various plant and worker characteristics to the rise in German wage dispersion. Moreover, we separately investigate the sources of between‐plant and within‐plant wage dispersion. We find that industry effects and the collective bargaining regime contribute the most to rising wage inequality. In the case of collective bargaining, both the decline in collective bargaining coverage and the increase in wage dispersion among the group of covered plants have played important roles.

Offshoring and non-monotonic employment effects across industries in general equilibrium - Baumgarten, Daniel; Irlacher, Michael; Koch, Michael (European Economic Review)

Trade exposure and the decline in collective bargaining: Evidence from Germany - Baumgarten, Daniel; Lehwald, Sybille

Temporary Agency Work and the Great Recession - Baumgarten, Daniel; Kvasnicka, Michael (Journal of Economic Behavior and Organization)

Offshoring, the Nature of Tasks, and Occupational Stability: Empirical Evidence for Germany - Baumgarten, Daniel (The World Economy)
Abstract Using a large administrative data set of individual employment histories for Germany, this paper studies the relationship between offshoring and the individual risk of leaving the occupation. Moreover, a rich data set on tasks performed in occupations is used to better characterise the sources of worker vulnerability. Both material and service offshoring are, on average, not associated with an increase in occupational outflow rates. However, this association depends on the nature of tasks performed in the occupation. Higher intensities of interactive and, in particular, non‐routine tasks are associated with a larger decrease (or a smaller increase) in the occupational hazard rate.

International trade and worker flows: empirical evidence for Germany - Baumgarten, Daniel (Review of World Economics)

Foreign direct investment, heterogeneous workers and employment security: Evidence from Germany - Bachmann, Ronald; Baumgarten, Daniel; Stiebale, Joel (Canadian Journal of Economics)
Abstract We analyze how foreign direct investment (FDI) affects employment security using administrative microdata for German employees. Measuring FDI intensity at the industry level enables us to take into account the sum of direct effects at multinationals as well as indirect effects of FDI throughout the affected industry. We find that both inward and outward FDI significantly reduce employment security. This is particularly the case for inward FDI coming from the western part of the European Union as well as for outward FDI going to Central and Eastern Europe. The effects are sizeable for older and low‐skilled workers.

How do the unemployed search for a job? – Evidence from the EU Labour Force Survey - Bachmann, Ronald; Baumgarten, Daniel (IZA Journal of European Labor Studies)

Exporters and the rise in wage inequality: Evidence from German linked employer–employee data - Baumgarten, Daniel (Journal of International Economics)

Offshoring, tasks, and the skill-wage pattern - Baumgarten, Daniel; Geishecker, Ingo; Görg, Holger (European Economic Review)